Revision of the genus Canthocamptus (Copepoda: Harpacticoida) with a description of a new species from the Lena River Delta (North-eastern Siberia) - Novikov, Aleksandr; Sharafutdinova, Dayana (European Journal of Taxonomy, 2022)
The discovery of a new species of the genus Canthocamptus, C. waldemarschneideri sp. nov., in northern Siberia prompted a taxonomic analysis of this genus. In this work, on the basis of cladistic analysis, we show that the genus is not monophyletic. Based on differences in the structure of the endopods on the second pair of male swimming legs, fifth legs of males and females, and caudal rami, we conclude that the Canthocamptus mirabilis species group is a separate genus, Kikuchicamptus gen. nov. Additionally, two species are transferred to the genus Attheyella, and one species, Canthocamptus gibba, is synonymized. The subgenera Canthocamptus (Baikalocamptus) and Canthocamptus (Canthocamptus) are also synonymized. The new species, Canthocamptus waldemarschneideri sp. nov., is most closely related to the American Canthocamptus assimilis Kiefer, 1931 and differs from it in the ornamentation of the abdominal somites and the shape of the caudal setae.